Effect of nanoparticle additives on rough surface cylinder in line contact under TEHL with non-Newtonian lubricant - Mongkol MONGKOLWONGROJN; Sountaree RATTAPASAKORN (My University, 2014)
This paper presents the results of a transient analysis of thermal elastohydrodynamic lubrication (TEHL) of a rough cylinder on a rough flat surface in line contact with non-Newtonian lubricant blended with Al2O3 nanoparticles. The simultaneous systems of time-dependent modified Reynolds equation, elasticity equation and energy equation with initial conditions were solved numerically using multigrid multilevel with full approximation technique. In this study, the effect of Al2O3 nanoparticle additives, surface roughness and sudden overload on TEHL of two surfaces in line contact were examined. The minimum film thickness and the pressure spike increase slightly with an increase in nanoparticle concentration. For TEHL with Al2O3 nanoparticle additives, the film temperature increases very little due to thermal enhancement of nanofluids.
Keywords: Elasticity; Tribology and Lubrication Engineering